Prostate cancer incidence and mortality linked to metalworking fluid exposure: a systematic review and meta-analysis - Moradpour, Zahra; Barik, Amin; Jorjani, Goljamal; Taherian, Mohammad Reza; Tousizadeh, Sepideh; Halimi, Aram; Soleimani, Yaser; Karimian, Mobina; Khavari, Tina; Kalankari, Fateme Azizi; Asadipour, Fatemeh; Azari, Mojtaba; et al. (Frontiers in Oncology, 2025)
BackgroundProstate cancer is the second most diagnosed cancer in men globally, with high prevalence in North America, Europe, and Australia. Occupational exposures, including metalworking fluids (MWFs), have emerged as a potential risk factor for prostate cancer, yet comprehensive studies on this association are limited.ObjectiveThis study aims to systematically review and conduct a meta-analysis to examine the incidence and mortality of prostate cancer linked to MWF exposure.MethodsA systematic review and meta-analysis were conducted following the PRISMA guidelines. A comprehensive search strategy was developed to identify relevant studies from PubMed, Scopus, Embase, and Web of Science. Inclusion criteria encompassed studies reporting on the association between MWF exposure and prostate cancer incidence or mortality. Data extraction and risk of bias assessment were performed independently by two reviewers, with discrepancies resolved by a third reviewer. Statistical analyses were conducted using STATA version 17.ResultsThe search identified 1376 unique references, with 5 studies meeting the inclusion criteria for the meta-analysis. These studies, conducted in the USA, primarily involved auto workers and reported Standardized Mortality Ratio (SMR), Relative Risk (RR) and 95% Confidence Interval (95%CI) measures. Meta-analysis revealed an overall RR of 1.06 (95% CI: 1.01-1.11) for prostate cancer incidence and an overall SMR of 1.20 (95% CI: 1.09-1.31) for prostate cancer mortality, indicating a statistically significant increased risk and mortality among MWF-exposed workers.ConclusionsThese findings carry significant implications for workplace safety regulations. Given the observed association between MWF exposure and prostate cancer risk, it is imperative to minimize occupational exposure through the implementation of effective engineering controls, personal protective equipment, and substitution of less hazardous fluids. Regular health surveillance and education programs for workers in industries utilizing MWFs are also essential to mitigate risk. Additionally, regulatory agencies should consider revising exposure limits and safety guidelines to account for emerging evidence on the carcinogenic potential of newer MWF formulations.